CD28− and CD28lowCD8+ Regulatory T Cells: Of Mice and Men - Vuddamalay, Yirajen; van Meerwijk, Joost P. M. (Frontiers in Immunology, 2017)
Since the rebirth of regulatory (formerly known as suppressor) T cells in the early 90's, research in the field of immune-regulation by various T cell populations has quickly gained momentum. While T cells expressing the transcription factor Foxp3 are currently in the spotlight, several other T cell populations endowed with potent immunomodulatory capacities have been identified in both the CD8+ and CD4+ compartment. The fundamental difference between CD4+ and CD8+ T cells in terms of antigen recognition suggests non-redundant, and perhaps complementary, functions of regulatory CD4+ and CD8+ T cells in immune-regulation. This emphasizes the importance and necessity of continuous research on both sub-populations of regulatory T cells so as to decipher their complex physiological relevance and possible synergy. Two distinct CD8-expressing regulatory T cell-populations can be distinguished based on expression of the co-stimulatory receptor CD28. Here we review the literature on these (at least in part) thymus-derived CD28low and peripherally induced CD28neg CD8+ regulatory T cells.